2016
DOI: 10.21608/jssae.2016.39788
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bio Fertilizer, Nitrogen and Sulfur Levels on Maize Production in Saline Soil of North Delta of Egypt

Abstract: Two field experiments were carried out at El-Serw agricultural Research Station, Governorate of Damietta through growing summer seasons of 2014 and 2015. The aim of the investigation is to study the effects of N bio fertilization (cyanobacteria, Azotbacter, Phosphorine and without inoculation), mineral sulfur applications (0, 15 and 30 kg S fed-1) and mineral nitrogen fertilization (0, 60 and 120 kg fed-1) on growth of the maize crop. Results showed that Cyanobacteria inoculation + 30 kg S fed-1 + 120 kg N fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Molina et al (2017) reported 22% improvement on plant height in case of bacteria inoculation at their 45 days experiment at greenhouse conditions. Additionally, a number of researchers are reported longer plants as a result of PGPR inoculation (Agbodjato et al, 2016;Ghaly et al, 2016;Jarak et al, 2012). No significant differences were observed between mean stem diameter values at different region isolates.…”
Section: Effects Of Pgpr On Growth Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Molina et al (2017) reported 22% improvement on plant height in case of bacteria inoculation at their 45 days experiment at greenhouse conditions. Additionally, a number of researchers are reported longer plants as a result of PGPR inoculation (Agbodjato et al, 2016;Ghaly et al, 2016;Jarak et al, 2012). No significant differences were observed between mean stem diameter values at different region isolates.…”
Section: Effects Of Pgpr On Growth Parametersmentioning
confidence: 99%
“…These mechanisms are referred as direct and indirect effects in the literature. Direct mechanisms are symbiotic and non-symbiotic nitrogen fixation (Hubbell and Kidder, 2003;Pereg et al, 2016;Ghaly and Alanos, 2016;Youseif, 2018;Richard et al, 2018;Fukami et al, 2018;) production of phytohormones such as auxin, gibberellin and cytokine, preventing ethylene production via 1-aminosiklopropan-1karboksilat (ACC) deaminase activity, reducing environmental stress factors (Dar et al, 2018;Glick 2014;Ali and Kim, 2018) increasing the solubility of inorganic phosphorus and mineralization of organic phosphorus compounds (Richardson et al, 2009;Zaidi et al, 2009;Zhang et al, 2014;Khosravi et al, 2018;Singh and Gera, 2018), increasing K uptake (Meena and Verma, 2014) and producing siderophore to improve Fe carriage to inner root zone (Patel et al, 2018;Dimkpa et al, 2009;Sandy and Butler, 2009). Indirect mechanisms include the reduction of the harmful effects of plant pathogens via enzyme production such as chitinase, cellulase, 1,3 glucanase, protease, lipase (Kundan et al, 2015), antibiotic secretion (Labuschagne et al, 2010) and inhibiting the establishment of phytopathogens by sequestration iron from the environment (Glick, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation